The Effect Of Entrepreneurship Knowledge, Entrepreneurship Motivation, E-Commerce, And Use Of Social Media on Interest in Entrepreneurship at Post-Pandemic Covid-19 (Research Study in Women Generation Z in Medan) - Alawi Fathan Yasin (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The purpose of this study is to ascertain the impact of entrepreneurship knowledge, motivation for entrepreneurship, e-commerce, and social media use on an individual's interest in entrepreneurship (a research study on women of generation Z in Medan City). variables, both independent and dependent. This study employs an associative technique in conjunction with a quantitative approach. The population and samples used in this study are as follows: age (20-24) with individual sex (Female) 130,549 souls and a sample of 101 women of generation Z in Medan City. The findings of this study reveal that entrepreneurial knowledge and motivation have a substantial effect on entrepreneurial interest, however e-commerce and social media use have no significant effect.